Effect of NPK on Ganoderma boninense sp. suppression on oil palm seedlings measured by proximal sensing - Khalid, Siti Noraishah (2015)
The Malaysian palm oil industry contributes RM61.29 billion in Malaysian export earnings for 2013. However, basal stem rot (BSR) caused by fungi Ganoderma boninense is a major problem in many oil palm plantations, especially in Indonesia and Malaysia since it known as the only pathogenic disease causing significant losses of oil palm plantation in South-East Asia. Many methods have been taken to control this disease, but to date no method gives good control of Ganoderma in established plantation. This is because the disease cannot be detected at the early stage, and when the disease symptoms do appear more than 50% of internal tissues are already rotten additionally. There are little studies to the role of nutrition in reducing diseases of tropical tree. Adequate nutrition helps to reduce damage by replacement of root and shoot tissues. Destructive sampling is necessary to examine dry mass and nutrient content of leaves, but this method is quite labour intensive and time consuming. Proximal sensing can offer the opportunity to rapidly collect a huge amount of information regarding the crop canopy and identify plant needs non-destructively. Therefore, this study is conducted to investigate effect of Nitrogen (N), Phosphorous (P), and Potassium (K) treatments toward suppression of Ganoderma boninense on oil palm seedlings and to examine and analyze the reflectance of the infected oil palm seedlings using proximal sensors. In this study, data from Ganoderma and healthy seedlings have been analyzed to determine the most effective treatment to suppress Ganoderma boninense base on their spectral reflectance, chlorophyll contents and the foliar analysis. The result showed that N-excessive and K-excessive treatments have a potential to suppress Ganoderma boninense since Ganoderma seedlings responded as good as healthy seedlings where N, P, and K contents between Ganoderma and healthy seedlings were not significantly different. In N-excessive treatment, Ganoderma seedlings showed higher P and K reading than healthy seedlings. SPAD reading was able to compare relative chlorophyll content between healthy and Ganoderma seedlings but failed to discriminate between different fertilizer treatments. In contrast, spectraradiometer was successful to compare spectra reflectance between healthy and Ganoderma seedlings at four different wavelengths which are blue, red, green, and infrared wavelengths. Therefore, these treatments can be field tested on oil palms as fertilization programme in order to suppress Ganoderma boninense.